2003
DOI: 10.1002/cncr.11482
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression levels of NCOA3, TOP1, and TFAP2C in breast tumors as predictors of poor prognosis

Abstract: BACKGROUNDAmplification of DNA in certain chromosomal regions plays a crucial role in the development and progression of human malignancies, specifically when protooncogenic target genes within those amplicons are overexpressed. Comparative genomic hybridization studies have revealed frequent amplification at 20q in primary breast tumors. The aim of the current study was to identify specific genes in the 20q amplicon that were likely to have clinical significance.METHODSThe authors examined 38 primary breast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 33 publications
4
72
1
3
Order By: Relevance
“…Some of them had also previously demonstrated to be independent prognostic factors, i.e., RAF1, 24 KRT15, 25 WIF1, 26 KRT5, 40 MSH6 31 and NCOA3/AIB-1. 42 A GO analysis demonstrated significant probability of enrichment in biosynthetic and metabolic processes with an overrepresentation of amine metabolism classes, while pathway analysis showed significant enrichment in the urea cycle and in the amino group or proline metabolisms, in agreement with class representation (Table II). A borderline level of significance was also attained by cell cycle and insulin signaling pathways.…”
Section: Identification Of Genes Potentially Associated With Breast Csupporting
confidence: 61%
“…Some of them had also previously demonstrated to be independent prognostic factors, i.e., RAF1, 24 KRT15, 25 WIF1, 26 KRT5, 40 MSH6 31 and NCOA3/AIB-1. 42 A GO analysis demonstrated significant probability of enrichment in biosynthetic and metabolic processes with an overrepresentation of amine metabolism classes, while pathway analysis showed significant enrichment in the urea cycle and in the amino group or proline metabolisms, in agreement with class representation (Table II). A borderline level of significance was also attained by cell cycle and insulin signaling pathways.…”
Section: Identification Of Genes Potentially Associated With Breast Csupporting
confidence: 61%
“…In normal breast epithelium, PTK6 is low or undetectable, but the protein is overexpressed in many breast carcinomas (Petro et al, 2004;Zhang et al, 2005), suggesting, PTK6 expression is related to carcinogenesis. In contrast, high levels of PTK6 are expressed in some differentiating epithelial tissues such as normal gastrointestinal tract, skin (Llor et al, 1999;Haegebarth et al, 2004), and prostate (Derry et al, 2003), and PTK6 expression was associated with the degree of differentiation of breast tissue as indicated by ER expression (Zhao et al, 2003). The correlation of PTK6 protein expression with the histological tumour grade observed in our study may also support an association between PTK6 and cell differentiation.…”
Section: Discussionsupporting
confidence: 50%
“…Overexpression of PTK6-mRNA positively correlates with hormone receptor status (Zhao et al, 2003) and HER2/NEU expression (Born et al, 2005) in breast cancer specimens. Several in vitro studies of PTK6 point to a possible role in modulating signal transduction of receptor tyrosine kinases (RTKs): PTK6 expression increases HER3 phosphorylation and Akt activation (Kamalati et al, 2000;Zhang et al, 2005), sensitises cells to epidermal growth factor (EGF) (Kamalati et al, 1996), which activates PTK6 (Kamalati et al, 2000;Chen et al, 2004), and influences the apoptotic pathway (Haegebarth et al, 2005).…”
mentioning
confidence: 99%
“…49 Recently, it was reported that TOP1, TFAP2C and NCOA3 (AIB1) might be prognostic indicators in breast cancer. 50 The NCOA3 gene encodes a coactivator of steroid receptor that interacts with estrogen receptors to enhance ligand-dependent transcription. The TOP1 gene encodes topoisomerase 1, a nuclear enzyme that catalyzes single-strand breakage and rejoining of DNA, allowing the relaxation of supercoiled DNA during transcription and DNA replication.…”
Section: Discussionmentioning
confidence: 99%